Be Open and See Where Your Path Leads: Dr. Judy Voress. (January 2021) - Higgins, Kyle; Boone, Randall
Dr. Judy Voress is the former periodicals director of PRO-ED; is Executive Director and a member of the Board of Directors of the Hammill Institute on Disabilities; and currently serves as President and a Trustee of the Donald D. Hammill Foundation, a philanthropic organization focused on improving the quality of life for individuals with disabilities, the elderly, and those with financial challenges. Her professional background also includes time spent as a special education teacher, university assistant professor, associate journal editor, adjunct university professor, and author of educational tests and materials.